Um ambiente de suporte ao trabalho cooperativo com aplicação à telemedicina - Nascimento, Alessandra Mendes Pacheco (2002)
This dissertation presents a cooperative virtual multimedia enviroment for employing on time medical Field, using a TCP/IP computer network. The Virtual Diagnosis Room environment make it possible to perform cooperative tasks using classical image processing. Synchronous and assynchronous text conversation (chat) and content markup, in order to produce remote cooperative diagnosis. The dissertation also describes the tool in detail and its functions, that enables the interaction among users, along with implementation detals, contributions and weakness of this work